A preliminary investigation into the internal consistency and construct validity of the Triple C: Checklist of Communicative Competencies - TERESA IACONO KAREN BLOOMBERG and DENISE WEST (Journal of Intellectual & Developmental Disability, September 30(3) 2005 pp.139-145, 2005)
Background The Triple C was designed to assess the communication skills of people with severe disabilities and to sensitise support workers to their communicative behaviours. The study aim was to investigate the Triple C's internal consistency and construct validity. Method Deidentified data from the completed checklists of 172 adults with severe disabilities were collected. Results Overall internal consistency was found to be high. Internal consistency was found to be high also for Stages 2 to 6, and acceptable for Stage 1. A measure of association between item and stage totals indicated a hierarchy of skills. Although the factor analysis revealed two underlying factors, most stages loaded highly onto only one factor, interpreted to be early intentional-presymbolic communication. Conclusions. The results indicated good internal consistency, and promising construct validity. They also pointed to a need to modify the Triple C for both clinical and research purposes.